Evaluation of the impact of abuse deterring agents on the physicochemical factors of tramadol-loaded tablet and the definition of new abuse deterrent index - Won, Dong Gyu; Park, Guilea; Ngo, Hai V.; Jin, Gang; Park, Chulhun; Lee, Beom Jin (International Journal of Pharmaceutics, 2021)
In the design of abuse-deterrent formulations (ADFs), pharmaceutical strategies that do not modify the physical and chemical properties of opioid dosage forms should be investigated. Among these, four major drug abusing factors, including particle size by physical modification, swellability, dissolution rate, and solvent extraction, were mainly characterized for evaluating abuse deterrence of narcotics. Tramadol hydrochloride (TMD) was chosen as a model drug. In this study, the frequently used eight generally recognized as safe (GRAS)-listed pharmaceutical excipients, including polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HPMC 4,000, HPMC 100,000), xanthan gum (XG), cellulose acetate (CA), polyethylene oxide (PEO), carbomer 940 NF, and Compritol® 888 ATO, were selected as abuse deterring agents and used to prepare TMD-loaded tablet. A new abuse-deterrent index (ADI) for compressed TMD-loaded tablets was originally defined and considered as an index of drug abuse deterrence, based on the assumption that it was proportional to particle size and swellability but inversely proportional to dissolution and solvent extraction rates after assigning the categorized five scale scores (one to five) to the four experimental data. The resulting ADI of the selected eight abuse deterring agents in deionized water was given in decreasing order: HPMC 4000 > carbomer 940 > Compritol® 888 ATO > XG > PVA > HPMC 100,000 > PEO, and CA while in 40% hydro-alcoholic solution in the decreasing order: carbomer 940 > HPMC 4,000 ≒ XG > PVA > HPMC 100,000 > PEO > Compritol® 888 ATO > CA. Interestingly, the HPMC 4,000 and carbomer 940 showed the highest ADI and gave drug abuse deterrent potential. This study could provide a pharmaceutical strategy that utilizes a variety of abuse-deterring agents and resist to extraction solvents in designing drug abuse-deterrent formulations and establishing their standard guidelines for regulatory authorities.
Keywords: Delayed-Action Preparations; Drug Compounding; Excipients; Hypromellose Derivatives; Tablets; Tramadol; Abuse deterring agents; Abuse-deterrent index; Dissolution rate; Particle size; Solvent extraction; Swellability; Tramadol